Strategic Defect Engineering of Metal–Organic Frameworks for Optimizing the Fabrication of Single‐Atom Catalysts - He, Jie; Li, Na; Li, Zhi‐Gang; Zhong, Ming; Fu, Zi‐Xuan; Liu, Ming; Yin, Jia‐Cheng; Shen, Zhurui; Li, Wei; Zhang, Jijie; Chang, Ze; Bu, Xian‐He (Advanced functional materials, 2021)
Single‐atom catalysts (SACs) have garnered enormous interest due to their remarkable catalysis activity. However, the exploitation of universal synthesis strategy and regulation of coordination environment of SACs remain a great challenge. Herein, a versatile synthetic strategy is demonstrated to generate a series of transition metal SACs (M SAs/NC, M = Co, Cu, Mn; NC represents the nitrogen‐doped carbon) through defect engineering of metal‐organic frameworks (MOFs). The interatomic distance between metal sites can be increased by deliberately introducing structural defects within the MOF framework, which inhibits metal aggregation and consequently results in an approximately 70% increase in single metal atom yield. Additionally, the coordination structures of metal sites can also be facilely tuned. The optimized Co SAs/NC‐800 exhibits superior activity and excellent reusability for the selective hydrogenation of nitroarenes, surpassing several state‐of‐art non‐noble‐metal catalysts. This study provides a new avenue for the universal fabrication of transition metal SACs. A general metal–organic framework defect engineering strategy is proposed to increase the yield of single‐atom catalysts. This strategy enlarges the distance between metal active sites, effectively hindering the aggregation of metal atoms and affording a 70% improved yield of metal single atoms. The optimized Co SAs/NC‐800 exhibits superior activity and reusability in nitroarene hydrogenation.